Pengaruh Aerobik Intensitas Ringan terhadap Risiko Jatuh Lansia berdasarkan Skor Time Up and Go - Puspitosari, Aniek; Nurhidayah, Ninik (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Falls in the elderly are a common problem due to several factors such as internal and external factors. Providing physical activity in the elderly to reduce the incidence of disability and death due to falls in the elderly. One of the physical activities that can prevent falls in the elderly is low impact aerobics. Objectives: This study aims to determine the effect of low impact aerobics on the risk of falls in the elderly. Methods: This study used a pre experimental one group pretest and posttest method with a sample size of 30 elderly people in Kebakkalang RT III RW VIII Kemiri Kebakkamat Karanganyar. The research instrument used Time Up And Go (TUG). Ten low impact aerobic movements were given each intervention based on the research module that had been compiled. The data analysis method uses paired t-test with the previous stage, namely data normality test with Shapiro Wilk. Results: The paired t-test results showed that the sig value was <0.05. An increase in TUG score occurred after the intensitas ringan aerobics intervention (mean difference 0.582). Low impact aerobics has an effect on the risk of falling for the elderly ( ????=0.000). The research sample was 80% female, 95% dominated by the age group 56-65 years. Conclusion: This study shows that low impact earobics intervention has a significant effect on the risk of falls in the elderly. Keywords: Aging, Exercise, Balance